2014
DOI: 10.1021/ja505126v
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Distinct Electron Transfer Processes in Terminal Oxidases from Different Origin by Means of Protein Film Voltammetry

Abstract: Cytochrome aa3 from Paracoccus denitrificans and cytochrome ba3 from Thermus thermophilus, two distinct members of the heme–copper oxidase superfamily, were immobilized on electrodes modified with gold nanoparticles. This procedure allowed us to achieve direct electron transfer between the enzyme and the gold nanoparticles and to obtain evidence for different electrocatalytic properties of the two enzymes. The pH dependence and thermostability reveal that the enzymes are highly adapted to their native environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…1 shows the catalytic current obtained for wild type (black line), K354M (dotted line), D124N (dark grey) variants and the D124N/K354 double variant (light gray) of CcO from P. denitrificans . The reduction of oxygen in the wild type CcO from P. denitrificans immobilized on gold nanoparticles takes place at – 0.18 V [23]. In the different variants studied, a down shift of the reduction potential to values around – 0.28 V takes place, pointing towards a slower reduction.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1 shows the catalytic current obtained for wild type (black line), K354M (dotted line), D124N (dark grey) variants and the D124N/K354 double variant (light gray) of CcO from P. denitrificans . The reduction of oxygen in the wild type CcO from P. denitrificans immobilized on gold nanoparticles takes place at – 0.18 V [23]. In the different variants studied, a down shift of the reduction potential to values around – 0.28 V takes place, pointing towards a slower reduction.…”
Section: Resultsmentioning
confidence: 92%
“…The technique is based on porous three‐dimensional gold nanoparticle electrodes obtained by drop‐casting a concentrated gold colloid on the surface of a polycrystalline gold substrate. These electrodes allow both an exceptionally high surface coverage and a reversible direct electron transfer with the immobilized enzyme [22–24]. After immobilization of CcO, the catalytic current and the oxygen reduction potential can be investigated in presence of oxygen [23].…”
Section: Introductionmentioning
confidence: 99%
“…Peak positions and current densities could be verified by our modelling studies based on the model shown in Schematic 2 performed under anaerobic and aerobic conditions [13,15]. The shifted redox potential was later confirmed by protein-film voltammetry of terminal oxidases aa 3 from a different origin as well as CcO from P. denitrificans, respectively, albeit explained in terms of oxygen reduction catalysed by CcO [16,17]. Schematic 1 reveals how the redox centers discernable by their porphyrin rings are closely embedded within protein secondary structures such as -helices and -sheets.…”
Section: Introductionmentioning
confidence: 55%
“…The enzymes were immobilized on electrodes modified with gold nanoparticles of 15 nm average diameter, following a procedure previously described . The gold NPs were prepared by the procedure of Turkevich et al .…”
Section: Methodsmentioning
confidence: 99%